Pemanfaatan Mina Padi di Kawasan Pertanian Desa Jatisarono - Dharomesz, Vonezyo Yupanzara (Jurnal Atma Inovasia, 2022)
Jatisarono Village is a village in Kulon Progo Regency that has potential in terms of agriculture. However, the potential of agriculture is still not widely developed by the community around Jatisarono Village in more depth. The potential of agriculture can be marketed by spreading it through existing tourism places and also by developing the land around the farm by doing mina padi and explaining how to use mina padi into a good tourist area through good marketing as well. The purpose of KKN activity is to be a forum for students to work, provide an explanation of the village’s potential, then provide knowledge about what are the benefits of mina padi for the surrounding community, increase empathy and concern for the surroundings, realizing a sense of responsibility and solidarity,  and foster a disciplined attitude in working together. This KKN consists of several externals or outputs, including village potential e-books and videos, mina padi's ebooks and pocketbook videos and KKN reports. KKN 80 is organized through KKN groups consisting of 10 people and individual KKN. as well as the location of our KKN located in Jatisarono Village, Kapanewon Nanggulan, Kulon Progo Regency, DIY.